Traceability of contributions in the co-creation of products/services: A case study in a telecommunications company [Trazabilidad de contribuciones en la co-creación de productos/servicios: Un estudio de caso en una empresa de telecomunicaciones] (2014)
The traceability of contributions in the joint creation between customers and organizations (co-creation), is recognize as a fundamental task to support activities in obtaining products/services with high potential for innovation. The goal of traceability is to improve the quality of products and services. The information that provides the traceability can be used to support the analysis of the implications and integration of change requests in different phases of innovative models and to understand the evolution of artifacts that represent the knowledge. This work presents a model that facilitates following the contributions of stakeholders that participate in co-creation of a service for video transmission in a telecommunications organization in Medellin, Colombia. The proposed model allows to track the contributions generated and the results corroborate the establishment of relationships between artifacts at different stages of the innovation cycle.